Does Utilitarian Policy such as Smoking Cessation Lend Support to Wider Aspirin Use? - Gareth Morgan (AIMS Press, 2015)
Tobacco control policy seems to be based on a utilitarian principle that public health is best served by a range of measures that will provide overall population benefit. Aspirin may have a potential wider role since meta-analysis of randomized controlled trials shows it reduces the risk of a first vascular event and also cancer. Are smoking cessation and the public health potential of aspirin different? The benefit versus risk balance of aspirin, an inexpensive and easily available medicine, deserves serious consideration as a public health measure in middle age. Smoking cessation and wider aspirin use are not seen as either competing or duplicating policy areas, but complementary. Their comparison has been purposefully selected because of common impacts, namely reduced vascular disease and cancer with increases in undesirable effects, notably gastrointestinal pathology. Part of the driver for this paper is to convey the message that public health policy has benefits and risks and the concept of a universally effective policy is unrealistic. Is it time for public health action to increase the use of aspirin?